Uso de los ciclos de aprendizaje para la enseñanza de destrezas de razonamiento científico y de sistemas conceptuales - Lawson, A. E. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1994)
This paper deals with an important tool in science education, learning cycles. The author covers this topic through a historical perspective about their origins, a theoretical position about their use (covering the nature of declarative and procedural knowledge and the constructive process of formation of concepts and the relationship of the latter with conceptual change), and concludes with a description of the three types learning cycles and their accomplishment of improving students' declarative and procedural knowledge. The examples along the text are specially devoted to biology.